2020
DOI: 10.1007/s10339-019-00947-6
|View full text |Cite
|
Sign up to set email alerts
|

Feature distinctiveness effects in language acquisition and lexical processing: Insights from megastudies

Abstract: Semantic features are central to many influential theories of word meaning and semantic memory, but new methods of quantifying the information embedded in feature production norms are needed to advance our understanding of semantic processing and language acquisition. This paper capitalized on databases of semantic feature production norms and age-of-acquisition ratings, and megastudies including the English Lexicon Project and the Calgary Semantic Decision Project, to examine the influence of feature distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In layperson terms, Manhattan distance is sensitive to the extent to which features differ between two words. Although there are other ways of computing distance, previous investigations by Engelthaler and Hills (2017) and Siew (2020) showed that feature distinctiveness computed with Manhattan distance was a stronger predictor of behavioral data as compared to other distance measures such as Jaccard distance.…”
Section: Methodsmentioning
confidence: 99%
“…In layperson terms, Manhattan distance is sensitive to the extent to which features differ between two words. Although there are other ways of computing distance, previous investigations by Engelthaler and Hills (2017) and Siew (2020) showed that feature distinctiveness computed with Manhattan distance was a stronger predictor of behavioral data as compared to other distance measures such as Jaccard distance.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have sought to model early vocabulary networks to describe early patterns in lexical acquisition in relation to productive vocabulary size. These studies have varied in their approach to establishing semantic connections among words, variously using: free association norms (Fourtassi et al, 2020; Hills et al, 2009b); child-directed speech corpora derived co-occurrence statistics (Beckage et al, 2011); semantic features (Hills et al, 2009a, 2009b; Peters & Borovsky, 2019; Siew, 2019; Yurovsky et al, 2012); or a combination of all of these (Stella et al, 2017). All of these approaches yield appropriate measures of semantic structure in early lexicon, and studies that have sought to compare multiple semantic modeling methods in psycholinguistic studies have found a number of redundancies in among feature norm and distributional approaches (Riordan & Jones, 2011).…”
Section: Drivers Of Lexical Processingmentioning
confidence: 99%
“…Again, large databases of feature production norms are readily available for researchers to analyze the internal conceptual structure of words [38]. Feature networks can be constructed by connecting concepts that share the same features, and network analysis of feature networks have provided new insights into language development [39,40] and semantic processing [41]. Within the context of the education sciences, students could be asked to list features or properties of key concepts.…”
Section: Measuring Knowledge Structuresmentioning
confidence: 99%